Optimism and Mortality in Older Men and Women: The Rancho Bernardo Study - Ericha G. Anthony; Donna Kritz-Silverstein; Elizabeth Barrett-Connor (Journal of Aging Research)
Purpose. To examine the associations of optimism and pessimism with all-cause, cardiovascular disease (CVD), coronary heart disease (CHD), and cancer mortality in a population-based sample of older men and women followed ≤12 years. Methods. 367 men and 509 women aged ≥50 from the Rancho Bernardo Study attended a 1999–2002 research clinic visit when demographic, behavioral, and medical history were obtained and completed a 1999 mailed survey including the Life Orientation Test-Revised (LOT-R). Mortality outcomes were followed through 2012. Results. Average age at baseline was 74.1 years; during follow-up (mean = 8.1 years), 198 participants died, 62 from CVD, 22 from CHD, and 49 from cancer. Total LOT-R, optimism and pessimism scores were calculated. Participants with the highest optimism were younger and reported less alcohol use and smoking and more exercise. Cox proportional hazard models showed that higher total LOT-R and optimism, but not pessimism scores, were associated with reduced odds of CHD mortality after adjusting for age, sex, alcohol, smoking, obesity, physical exercise, and medication (HR = 0.86, 95% CI = 0.75, 0.99; HR = 0.77, 95% CI = 0.61, 0.99, resp.). No associations were found for all-cause, CVD, or cancer mortality. Conclusions. Optimism was associated with reduced CHD mortality in older men and women. The association of positive attitudes with mortality merits further study.